2015
DOI: 10.4149/neo_2015_017
|View full text |Cite
|
Sign up to set email alerts
|

Molecular cytogenetic analyses of hTERC (3q26) and MYC (8q24) genes amplifications in correlation with oncogenic human papillomavirus infection in Czech patients with cervical intraepithelial neoplasia and cervical carcinomas

Abstract: It is known that cervical cancer develop from precancerous intraepithelial neoplasia (CIN) which is characterized by series of genetic abnormalities. The progression of CIN to cervical carcinoma has been associated especially with the genomic integration of oncogenic human papilloma virus (HPV) and gain of the human telomerase RNA gene hTERC (3q26) and MYC (8q24).In this study, cytology specimens of cervical intraepithelial neoplasia and cervical carcinoma from 74 Czech women were analyzed using the triple-col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 25 publications
0
14
0
2
Order By: Relevance
“…These results agree with previous studies reporting a comparable incidence for the amplification of the entire 3q26 region in precancerous cervical lesions and cervical cancer [41], suggesting that the SEC62 gene harbors an oncogenic function. However, there are other potential 3q26-encoded oncogenes with a similar pattern of amplification and overexpression in dysplastic cervical lesions including hTERC , LAMP3 and PIK3CA [4245]. Kuglik et al reported that gains of the hTERC gene are specific genomic changes in cytological specimens of the uterine cervix associated with the progression to a malignant phenotype [42].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results agree with previous studies reporting a comparable incidence for the amplification of the entire 3q26 region in precancerous cervical lesions and cervical cancer [41], suggesting that the SEC62 gene harbors an oncogenic function. However, there are other potential 3q26-encoded oncogenes with a similar pattern of amplification and overexpression in dysplastic cervical lesions including hTERC , LAMP3 and PIK3CA [4245]. Kuglik et al reported that gains of the hTERC gene are specific genomic changes in cytological specimens of the uterine cervix associated with the progression to a malignant phenotype [42].…”
Section: Discussionmentioning
confidence: 99%
“…However, there are other potential 3q26-encoded oncogenes with a similar pattern of amplification and overexpression in dysplastic cervical lesions including hTERC , LAMP3 and PIK3CA [4245]. Kuglik et al reported that gains of the hTERC gene are specific genomic changes in cytological specimens of the uterine cervix associated with the progression to a malignant phenotype [42]. Furthermore, a meta-analysis of 12 studies evaluating the diagnostic value of hTERC in dysplastic cervical lesions found that the detection of hTERC amplification is a valuable marker for high-grade cervical lesions and invasive cancer [43].…”
Section: Discussionmentioning
confidence: 99%
“…Molecular cytogenetic analysis by FISH technique was accomplished using the commercial kit Vysis Cervical FISH Probe (Abbott Molecular, Illinois, USA). The kit enables the simultaneous detection of HPV-infected cells and the amplification of chromosomal regions 3q26 (hTERC gene) and 8q24 (MYC gene) as described previously [7,25]. For the whole-genome screening of chromosomal abnormalities by array-CGH, we used a platform of oligonucleotide-based DETECTION OF MUTATIONS IN CERVICAL CARCINOMA By METHOD HRM DNA microarrays SurePrint G3 CGH+SNP Array 180K (Agilent Technologies, Santa Clara, CA, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Consequently we evaluated the results of mutation analysis in the relationship to clinical characteristics of the disease. Simultaneously, we studied possible correlations between the gene mutations or DNA sequence changes and the presence of chromosomal abnormalities which were detected by methods of HPV-FISH (fluorescence in situ hybridization for the detection of human papillomavirus in cells) and array-CGH (array-based comparative genomic hybridization) realized in the scope of our previous studies [7,25].…”
mentioning
confidence: 99%
“…Не менее важным маркером при высокой степени неоплазии и инвазивном раке шейки матки оказалась также амплификация локуса 8q24 (ген С-MYC) [42]. Хотя у пациенток с цервикальной карциномой амплификация этого гена наблюдалась в меньшей степени по сравнению с ча-стотой гена hTERC (25 и 62,5% соответственно) [50].…”
unclassified